Research of the Transmission Characteristic of Planetary Gear Train based on the Signal Flow Graph Method - Zhou Xintao; Cui Yahui; Yan Haitao; Li Longlong (Jixie chuandong)
Based on the transmission principle of planetary gear train,a method by using the signal flow graph is proposed to calculate the torque of complex planetary gear train. By combining the structure characteristics of transmission chain of planetary gear train with the transfer characteristic of signal flow,the signal flow graph models of compound system of XP type,PX type,T type,∏ type and E type of planetary gear train are established. The signal flow graph is used to simplify the calculation of topology model by using signal flow graph,the calculation formula of characteristic parameters for each component is obtained. The results show that this method has good visibility and high efficiency,a new method for the parameter calculation of complex planetary gear train is provided.